2016
DOI: 10.2166/wst.2016.521
|View full text |Cite
|
Sign up to set email alerts
|

Removal of mixture of ZnO and CuO nanoparticles (NPs) from water using activated carbon in batch kinetic studies

Abstract: The aim of this study was to understand the effects of pH (5, 6, 7, 8, 9) and activated carbon (AC) concentration (0.01, 0.1, 1, 10, 100 g/L) on the removal of a colloidal solution of nanoparticles (NPs) (ZnO + CuO) using AC in batch kinetic studies. Results revealed that adsorption capacities of AC for Zn and Cu (individually) were 0.9 ± 0.028 mg/g (91.3% removal) and 0.95 ± 0.036 mg/g (95.6% removal) in deionized water and 0.6 ± 0.038 mg/g (78% removal) and 0.75 ± 0.078 mg/g (83% removal) in wastewater at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…FT-IR was performed to investigate the function groups in AC-Cu, as shown in Figure . The broad absorption peak at approximately 3440 cm –1 was assigned to OH in the alcohol, carboxyl, and hydroxyl groups, or chemisorbed water. , The peak at approximately 1630 cm –1 was attributed to the CO stretching vibration, such as in quinones and lactones . The peak at 1080 cm –1 (on AC) corresponded to the CO stretching in esters, phenols, and carboxylic acids. , It was interesting to observe that the peak at 1080 cm –1 (AC) shifted to a high wavenumber (around 1090–1130 cm –1 ) in the AC-Cu samples, possibly due to the CO association the with copper species after CuO addition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FT-IR was performed to investigate the function groups in AC-Cu, as shown in Figure . The broad absorption peak at approximately 3440 cm –1 was assigned to OH in the alcohol, carboxyl, and hydroxyl groups, or chemisorbed water. , The peak at approximately 1630 cm –1 was attributed to the CO stretching vibration, such as in quinones and lactones . The peak at 1080 cm –1 (on AC) corresponded to the CO stretching in esters, phenols, and carboxylic acids. , It was interesting to observe that the peak at 1080 cm –1 (AC) shifted to a high wavenumber (around 1090–1130 cm –1 ) in the AC-Cu samples, possibly due to the CO association the with copper species after CuO addition.…”
Section: Resultsmentioning
confidence: 99%
“…The broad absorption peak at approximately 3440 cm −1 was assigned to OH in the alcohol, carboxyl, and hydroxyl groups, or chemisorbed water. 31,32 The peak at approximately 1630 cm −1 was attributed to the CO stretching vibration, such as in quinones and lactones. 33 The peak at 1080 cm −1 (on AC) corresponded to the CO stretching in esters, phenols, and carboxylic acids.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Piplai et al [57] investigated the impact of pH values of 5-9 and activated carbon concentrations of 0.01, 0.1, 1, 10, and 100 g/L on the removal efficiency of colloidal NPs (ZnO and CuO) from their solutions in batch kinetic experiments. Results indicated that at pH values of 8 (ZnO) and 6 (CuO), the adsorption potentials of activated carbon for ZnO-NPs and CuO-NPs (removal efficiency of NPs using activated carbon) were 0.9 (91.3%) and 0.95 (95.6%) mg/g in deionized water, respectively, and 0.6 (78%) and 0.75 (83%) mg/g in wastewater, respectively.…”
Section: Adsorptionmentioning
confidence: 99%
“…The removal of ZnO-NPs and CuO-NPs from a colloidal solution via sedimentation/settlement was also investigated (removal rate of < 5% for both NPs) [57]. In both single and blended solutions, the overall adsorption potential of ZnO-NPs and CuO-NPs using activated carbon was examined.…”
Section: Adsorptionmentioning
confidence: 99%
“…Several methods such as phytoremediation, coagulation and flocculation, membrane filtration, and adsorption have been assessed to find suitable methods for removing metal-containing NPs from water and wastewater [20][21][22][23][24][25][26]. Because of the drawbacks of other methods including fouling in membrane filtration and high volume of sludge in coagulation and flocculation process, the adsorption process has been reported as the most efficient and economical method [27].…”
Section: Introductionmentioning
confidence: 99%